Alcohol consumption and NHMRC guidelines: has the message got out, are people conforming and are they aware that alcohol causes cancer? - Jacqueline A. Bowden; Paul Delfabbro; Robin Room; Caroline L. Miller; Carlene Wilson (Elsevier, 2014)
Abstract Objective: To examine self‐reported alcohol consumption and relationships between consumption, awareness of the 2009 NHMRC guidelines of no more than two standard drinks per day, drinking in excess of the guideline threshold and perceptions of alcohol as a risk factor for cancer. Methods: Questions were included in annual, cross‐sectional surveys of approximately 2,700 South Australians aged 18 years and over from 2004 to 2012. Consumption data for 2011 and 2012 were merged for the majority of analyses. Results: In 2011 and 2012, 21.6% of adults drank in excess of the guideline threshold (33.0% males; 10.7% females). While 53.5% correctly identified the NHMRC consumption threshold for women, only 20.3% did so for men (39.0% nominated a higher amount). A large minority said they did not know the consumption threshold for women (39.2%) or men (40.4%). In 2012, only 36.6% saw alcohol as an important risk factor for cancer. Important predictors of excess consumption for men were: higher household income; and not perceiving alcohol as an important risk factor for cancer. Predictors for women were similar but the role of household income was even more prominent. Conclusions: Men were nearly three times as likely to drink in excess of the guidelines as women. The majority of the population did not see an important link between alcohol and cancer. Awareness of the latest NHMRC guidelines consumption threshold is still low, particularly for men. Implications: A strategy to raise awareness of the NHMRC guidelines and the link between alcohol and cancer is warranted.